Group psychology and political theory - Alford, C. Fred (Yale University Press, 1994)
In this innovative book, C. Fred Alford argues that the group - not the individual - is the most fundamental reality in society and that political theory has overlooked the insights of group psychology and leadership. Basing his argument on his experience with the Tavistock model of group learning (named for the institute in England where this method of group study originated), Alford asserts that small, unstructured, leaderless groups are the closest thing to the state of nature that political theorists write about. According to Alford, none of the familiar traditions in political theory - including modern state-of-nature theory, liberalism, communitarianism, postmodernism, and feminist theory - makes sense of the group experience. Most contemporary political theorists have erred in starting from the position of the individual and moving to an understanding of the individual's struggle to belong to the group and civil society. Instead, says Alford, political theorists should realize that the group is the state of nature, and that civil society is the product of the individual's struggle to separate from the group and develop a sense of self. Alford's book, like many of the traditional state-of-nature theories, includes an extended anthropological fable, a story about the state of nature that is intended to illustrate its principles.